Postural assessment in pen-and-paper-based observational methods and their associated health effects: a review. Issue 3 (2nd July 2016) - Sukadarin, Ezrin Hani; Deros, Baba Md; Ghani, Jaharah A.; Mohd Nawi, Nur Syazwani; Ismail, Ahmad Rasdan
Abstract : Introduction . This review describes standardized ergonomics assessment based on pen-and-paper observational methods for assessing ergonomics risk factors. Objective . The three main objectives are to analyze published pen-and-paper observational methods, to extract and understand the risk levels of each method and to identify their associated health effects. Methodology . The authors searched scientific databases and the Internet for materials from 1970 to 2013 using the following keywords: ergo, posture, method, observational, postural angle, health effects, pain and diseases. Postural assessments of upper arms, lower arms, wrists, neck, back and legs in six pen-and-paper-based observational methods are highlighted, extracted in groups and linked with associated adverse health effects. Results . The literature reviewed showed strengths and limitations of published pen-and-paper-based observational methods in determining the work activities, risk levels and related postural angles to adverse health effects. This provided a better understanding of unsafe work postures and how to improve these postures. Conclusion . Many pen-and-paper-based observational methods have been developed. However, there are still many limitations of these methods. There is, therefore, a need to develop a new pen-and-paper-based observational method for assessing postural problems.